Rising mortality and life expectancy differentials by lifetime earnings in the United States - Julian P. Cristia (Inter-American Development Bank, Research Department, 2009)
Are mortality and life expectancy differences by socioeconomic groups increasing in the United States? Using a unique data set matching high-quality administrative records with survey data, this study explores trends in these differentials by lifetime earnings for the 1983 to 2003 period. The results indicate a consistent increase in mortality differentials across sex and age groups. The study also finds a substantial increase in life expectancy differentials: the top-to-bottom quintile premium increased around 30 percent for men and almost doubled for women. These results complement recent research to point to almost five decades of increasing differential mortality in the United States.
Keywords: I12; J11; 330; Differential mortality; Life expectancy; Lifetime earnings; Trends; Sterblichkeit; Lebenseinkommen; Soziale Schicht; Geschlecht; USA